A formatação da Ouvidoria dentro do contexto da governança pública: uma proposta para a ouvidoria do Instituto Federal de Educação, Ciência e Tecnologia de Sergipe (IFS) - Malta Júnior, Regis Renner Vasconcelos (2016)
This research report aims to present a proposal to regulate and structure the Ombudsman of the Federal Institute of Technological Education of Sergipe (FIS) to act as internal body to support governance. The first part of the report deals with the evolution of the relationship between citizen and state with the rise of democratization processes and the impact of this scenario on the public property management paradigms. Then are exposed how concepts of governance, accountability, participation and social control are related to the activities of Ombudsman and finally discusses the role of the Ombudsman, its form of organization and the importance of being supported by a management model. The research strategy is classified as an exploratory study and the analyzed unit is the Ombudsman of FIS. The result of the work is a proposal of Internal Regiment with main focus on institutional transformation of the Ombudsman through a design that moves from its subordination and submission stage to the bureaucratic-patrimonial logic, preponderant in FIS. Highlights of the document are enrichment assignments, the new selection procedure, the constitution of mandate and powers, as well as aspects related to operational management. The content addressed in the regimental proposal was to grant the second delivery of the project, the Charter of Citizen Services Ombudsman. To harmonize the Statute and the General Regiment of FIS to the proposed ombudsman model, changes are suggested for these regulations. It is expected that with the adoption of the proposed model the Ombudsman exercises social criticism to the administrative system, surpasses the patrimonial domination within the spectrum of participatory governance with full citizen access. In this way, it can legitimize public governance as a manifestation of the popular will, especially in an institution whose purpose is to contribute to human becoming.